Combination of electroacupuncture and pharmacological treatment improves insulin resistance in women with polycystic ovary syndrome: Double-blind randomized clinical trial - Raden Muharam; Adiningsih Srilestari; Hasan Mihardja; Lydwina Juvanni Callestya; Achmad Kemal Harzif (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Acupuncture is a nonpharmacological treatment which has been known to improve ovulatory function in polycystic ovary syndrome (PCOS) women. Acupuncture modulates the somatic and autonomic nervous systems, which regulate endocrine and metabolic functions to impact ovulatory functions. Objective: To investigate the effectiveness of electroacupuncture (EA) and pharmacological combination therapy on improving insulin resistance in women with PCOS. Materials and Methods: This double-blind, randomized clinical trial was performed on 44 participants from March to September 2018 at Cipto Mangunkusumo National hospital, Jakarta, Indonesia. Participants were randomly allocated to treatment (true EA + medication) and control group (sham EA + medication) in a 1:1 ratio using a web-based computer random-number generator. Randomization was carried out by an independent project manager. Both groups received 12 sessions of acupuncture therapy and metformin as pharmacological therapy. Results: This study showed a significant decrease in the Homeostatic Model Assessment for Insulin Resistance index in the true EA + medication group before and after therapy (p = 0.014). Conclusions: The combination of EA and pharmacological therapy effectively improves insulin sensitivity in women with PCOS.